Irritable bowel syndrome: relationship of disorders in the transit of a single solid meal to symptom patterns. - Cann, P A (1983)
The time taken for a solid meal to pass through the stomach, small intestine, and colon was measured in 61 patients with irritable bowel syndrome, subdivided according to their presenting symptoms, and in 53 healthy volunteers. Small bowel transit times were significantly shorter in patients who complained predominantly of diarrhoea (3.3 +/- 0.3 vs 4.2 +/- 0.2 h; p = 0.01; n = 21) and significantly longer in patients who complained predominantly of constipation (5.4 +/- 0.3 vs 4.2 +/- 0.2 h; p less than 0.01; n = 23) or pain and distension (5.4 +/- 0.4 vs 4.2 +/- 0.2 h; p less than 0.01; n = 17) compared with controls. Whole gut transit times were shorter in patients who complained of diarrhoea (35 +/- 5 vs 53 +/- 4 h; p less than 0.01), and longer in patients with constipation (87 +/- 13 vs 53 +/- 4 h; p less than 0.05) compared with controls. No significant differences in gastric emptying rates were shown between any of the patient groups and normal controls. Thirty-four patients reported pain, particularly in the right iliac fossa, during the meal transit test, and in 25 of these (74%), the onset of the pain was associated with the arrival of residues of the test meal in the caecum. Our results indicate that irritable bowel syndrome should be considered a disease of the small intestine as well as the colon.